Axial Tensile Experiment of the Lap-Type Asymmetric K-Shaped Square Tubular Joints with Built-In Stiffeners - Zhihua Zhong; Peiyu Peng; Zheweng Zhu; Xiang Ao; Shiwei Xiong; Jinkun Huang; Lihong Zhou; Xiaochuan Bai (Buildings)
To study the mechanical properties of asymmetric K-shaped square tubular joints with built-in stiffening rib lap joints, axial tensile tests were carried out on one K-shaped joint without built-in stiffening ribs and four K-shaped joints with built-in stiffening ribs using an electro-hydraulic servo structural testing system. The effects of the addition of stiffening ribs and the welding method of the stiffening ribs on the mechanical properties were studied comparatively. The failure mode of the K-shaped joint was obtained, and the strain distribution and peak displacement reaction force in the nodal region were analyzed. A finite element analysis of the K-shaped joint was carried out, and the finite element results were compared with the experimental results. The results showed that the addition of transverse reinforcement ribs and more complete welds shared the squeezing effect of the brace on the chord. Arranging more reinforcing ribs in the fittings makes the chord more uniformly stressed and absorbs more energy while increasing the flexural load capacity of the fittings’ side plates. The presence of a weld gives a short-lived temperature increase in the area around the crack, and the buckling of the structure causes the surface temperature in the buckling area to continue to increase for some time. The temperature change successfully localized where the structure was deforming and creating cracks. The addition of the reinforcing ribs resulted in a change in the deformation pattern of the model, and the difference occurred because the flexural capacity of the brace with the added reinforcing ribs was greater than that of the side plate buckling.